In vitro Lipase Inhibitory Effect of Thirty Two Selected Plants in Malaysia - ONG, SIEW-LING; PANEERCHELVAN, SUGUNA; LAI, HOW-YEE; KOTESWARA RAO, NALAMOLU (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Background: Obesity is a metabolic disorder that results from imbalance between energy intake and expenditure. Among many approaches in the treatment of obesity, lipase inhibitory potential in natural products is the most sought after, due to its effects in decreasing fat absorption without altering any central mechanisms. Objective: The objective of this study was to evaluate anti-obesity lipase inhibitory activities from thirty two medicinal and food plants in Malaysia. Materials and Methods: In the present study, methanolic extracts of thirty two selected plants which are known to have ethnomedicinal values or food plants, were investigated for lipase inhibition properties using porcine pancreatic lipase assay (PPL: triacylglycerol lipase, EC 3.1.1.3) in vitro. Results: Among the thirty two local plant species examined, four plants exhibited inhibition activities of more than 15 %. Eleusine indica showed the highest pancreatic lipase inhibitory activity of 31.36 %, followed by ripe female mace of Myristica fragrans (20.23 %), Melastoma candidum (19.67 %), Phyla nodiflora (18.26 %), ripe male mace of Myristica fragrans (17.99 %), respectively. There is no significant difference between activity produced by Eleusine indica methanolic extract and the standard drug Orlistat. Conclusion: Crude methanolic extracts of Eleusine indica, Myristica fragrans, Melastoma candidum and Phyla nodiflora were found to be possible candidates for further studies to isolate potential pancreatic lipase inhibitor among the thirty two different plants screened. Â Keywords: Eleusine indica, in vitro lipase inhibitory activity, Melastoma candidum, Myristica fragrans, Phyla nodiflora